STRATEGIC MANAGEMENT ACCOUNTING INFORMATION, SERVICE QUALITY, AND KNOWLEDGE MANAGEMENT TO COMPANY PERFORMANCE: A LITERATURE REVIEW - Hafizh Billy Anisman; Fajar Gustiawaty Dewi; Reni Oktavia (Transpublika Publisher, 2024)
The objective of this study is to investigate the influence of Strategic Management Accounting Information, service quality, and Knowledge Management on institutional performance. Through the utilization of a literature review methodology, this research examines the SINTA and Scopus databases, which are valuable sources of Indonesian scholarly publications spanning the last ten years. By systematically organizing the findings, methodologies, and concepts in a chronological manner, this literature review offers a comprehensive overview of the research progress regarding the interplay between strategic management accounting, service quality, knowledge management, and performance. The effective integration of strategic management accounting plays a crucial role in optimizing strategic decision-making, managing resources, and enhancing the quality of healthcare services. Additionally, a focus on service quality variables such as patient safety and operational efficiency creates an environment that supports operational growth and establishes a strong reputation. The synergy among these elements is expected to make a significant contribution to the competitive landscape and the overall advancement of the institution in the future.